KARAKTERISTIK PENDERITA RINOSINUSITIS KRONIK DI RUMAH SAKIT SANTA ELISABETH MEDAN TAHUN 2011-2015 - Nova Sitinjak; Sori Muda Sarumpaet; Hiswani . (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2016)
Chronic Rhinosinusitis is an inflammation of nasal mucosa and paranasal sinuses that can be detected by the history of symptoms which suffered more than 12 weeks, and suitable with two major criteria or one major criterion plus two minor criteria. According to H. Adam Malik Hospital Medan data in 2006 there are 40 cases of  Chronic Rhinosinusitis and 24 cases in 2009. The purpose of the study is to know the characteristic of the Chronic Rhinosinusitis patient at Santa Elisabeth Hospital Medan in 2011-2015. The design of this descriptive research was the case series and the sampling technique was total sampling. Population and sample were 163 cases from all of the Chronic Rhinosinusitis patient. The collected data were secunder data which analyzed with Chi-Square. The result showed the biggest proportion of the patients with Chronic Rhinosinusitis were in 26-35 years group (21,4%), male (55,8%), Bataknese (85,3%), Protestants (67,5%), entrepreneur (28,2%), complaint of major symptom is nasal congestion (92,6%), complaint for minor is headache (71,8%), rhinosinusitis inmaxillary sinus (92,0%), total sinus that involved in single rhinosinusitis (63,8%), there is no history diseases (84,7%), 100% no complications, surgery (65,6%), the average of the inpatien period was 5,41 days or 6 days and the condition after recovery (68,1%). The Chi-Square result showed that there were no significant difference between age (p = 0,157); gender (p = 0,315); complaint (p = 0,680); medical management (p = 0,071) from the patient of Chronic Rhinosinusitis with the total involved sinus and between gender (p = 0,196) from the patient of Chronic Rhinosinusitis with history diseases and there were significant difference between the history of the disease Chronic Rhinosinusitis patient with the total involved sinus (p = 0,001). The Chronic Rhinosinusitis suggested to keep their environment cleaner, use the mask when they are in pollution area, no smoking, to improve our health with consume food with good nutrition and for Hospital suggested to complete the datas about the Chronic Rhinosinusitis patient especially about the patients’ education. Keywords:       Chronic Rhinosinusitis, Characteristics, Santa Elisabeth Hospital